Pemanfaatan Moodle Dalam Pembelajaran Menulis Teks Eksposisi Siswa SMA - Wantoro, Sri (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2021)
Abstract This Classroom Action Research (CAR) investigates the learning process of writing exposition text as an effort to campaign for food safety in class XI MIPA 1 (XI Science I) SMA N 2 Pangkalpinang through MOODLE in blended learning context. Based on the experience of being a teacher, it is difficult for students to produce exposition texts during the learning process. For this reason, this study aims to describe the learning process of writing exposition text with the theme of food safety. This study uses a qualitative approach to explore reflective attitudes, behaviors, and experiences. This CAR uses four cycles. The results showed that the socialization of food safety carried out by research assistants from BPOM in Pangkalpinang City was carried out for 45 minutes face to face in a classroom and continued with online discussions using MOODLE by utilizing the forum feature. Furthermore, of the 33 students in class XI Science 1, all of them wrote the exposition text and all students got an exposition text score of ≥ 70 (100%) assessed using the grammarly application. This means that learning exposition text with the theme of food safety by involving experts from BPOM in Pangkalpinang went well where the students reached 100% of the set of standard competency minimum. Abstrak Penelitian Tindakan Kelas (PTK) ini menginvestigasi proses pembelajaran menulis teks eksposisi sebagai sebuah upaya berkampanye keamanan pangan pada siswa kelas XI MIPA 1 SMA N 2 Pangkalpinang menggunakan MOODLE dalam konteks blended learning. Berdasar pengalaman menjadi guru, teks eksposisi sulit dihasilkan oleh siswa pada proses pembelajaran. Untuk itulah penelitian ini bertujuan menggambarkan proses belajar menulis teks eksposisi dengan tema keamanan pangan. Penelitian ini menggunakan pendekatan kualitatif untuk menggali sikap, perilaku, dan pengalaman yang bersifat reflektif. PTK ini menggunakan empat siklus. Hasil penelitian menunjukan bahwa sosialisasi keamanan pangan yang dilaksanakan oleh pembantu penenliti dari BPOM di Kota Pangkalpinang dilaksanakan selama 45 menit tatap muka di dalam kelas dan dilajutkan dengan diskusi online menggunakan MOODLE memanfaatkan fitur forum. Selanjutnya, dari 33 siswa di kelas XI MIPA 1 seluruhnya menulis teks eksposisi dan seluruh siswa mendapatkan skor teks eksposisi ≥ 70 (100%) dinilaia menggunakan aplikasi grammarly. Ini berarti bahwa pembelajaran teks ekposisi dengan tema keamanan pangan dengan melibatkan tenaga ahli dari BPOM di Pangkalpinang berjalan dengan baik dimana siswa 100% mencapai KKM yang ditetapkan.